2006
DOI: 10.1143/jjap.45.1066
|View full text |Cite
|
Sign up to set email alerts
|

Signal Quality Evaluation Method for Over-30-GB Blu-ray Discs

Abstract: We proposed a new signal quality evaluation method applying a sequenced amplitude margin (SAM) for over 30-GB Blu-ray discs (BDs), where the dominant error pattern differs from lower-density discs (23 -27-GB BDs), and conventional signal quality evaluation method such as maximum-likelihood sequence error (MLSE) lose accuracy. We experimentally confirmed the effectiveness of our new method for 30 -31.5-GB BDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As an effective quasi-error estimation method, SAMQES was reported in Ref. 13, which showed good correlations to the bER particularly in high-density BD systems beyond 30 GB. The definition of SAMQES is given by EQ.…”
Section: Signal Quality Evaluation Methods For High-density Recording:mentioning
confidence: 99%
“…As an effective quasi-error estimation method, SAMQES was reported in Ref. 13, which showed good correlations to the bER particularly in high-density BD systems beyond 30 GB. The definition of SAMQES is given by EQ.…”
Section: Signal Quality Evaluation Methods For High-density Recording:mentioning
confidence: 99%
“…Several methods for evaluating the quality of readout signals to estimate the bit error rate in a readout system with a PRML channel have been reported. [4][5][6][7][8][9] Since readout data is determined by mark edge positions, they should be detected and controlled precisely for writing. An index called ''edge-shift'' is often used to detect mark edge positions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that over 30 Gbyte/layer recording is possible with the PRð1; 2; 2; 2; 1ÞML method. 1,2) Multilayer recording is another solution for achieving large capacity. In multilayer recording, however, optical disc technology of more than 100 Gbyte was reported, which was a write-once type media.…”
Section: Introductionmentioning
confidence: 99%